Betulinic acid restores imatinib sensitivity in BCR‐ABL1 kinase−independent, imatinib‐resistant chronic myeloid leukemia by increasing HDAC3 ubiquitination and degradation. Issue 1 (13th January 2020) - Lu, Tingting; Wei, Danna; Yu, Kunlin; Ma, Dan; Xiong, Jie; Fang, Qin; Wang, Jishi
Abstract: Although imatinib (IM) has been demonstrated to be an efficient treatment in chronic myeloid leukemia (CML), some patients still experience IM resistance and disease relapse. Through in vitro studies, we observed that HDAC3 levels were elevated in BCR‐ABL1 kinase−independent, IM‐resistant primary cells from CML patients and in IM‐resistant K562 (K562R) cells and that downregulation of HDAC3 could enhance IM efficacy in K562R cells. Furthermore, betulinic acid (BA), a lupane‐type pentacyclic triterpenoid saponin isolated from birch trees, restored IM sensitivity in the BCR‐ABL1 kinase−independent, IM‐resistant primary cells and in K562R cells, as well as in primary CD34 + bone marrow cells from CML patients. We found that BA restored IM sensitivity through inhibition of HDAC3 accumulation in cells, and that this was mediated by BA‐dependent ubiquitination and degradation of HDAC3. BA at low dosage significantly increased IM antitumor effects on murine xenografts bearing K562R cells and inhibited HDAC3 expression in tumor tissue. Our findings demonstrated that HDAC3 is an essential factor in BCR‐ABL1 kinase−independent IM resistance, and that BA in combination with IM may be a novel treatment strategy for overcoming IM resistance in CML. Abstract : Through in vitro studies we observed that HDAC3 levels were elevated in BCR‐ABL1 kinase−independent, imatinib (IM)‐resistant primary cells from CML patients and in IM‐resistant K562 (K562R) cells and that downregulation of HDAC3 could enhance IM efficacy in K562R cells. Furthermore, betulinic acid (BA) treatment restored IM sensitivity in the BCR‐ABL1 kinase−independent, IM‐resistant primary cells and in K562R cells, as well as in primary CD34 + bone marrow cells from CML patients, which depended on HDAC3 ubiquitination and degradation induced by BA.